Makna Semantik dalam Mantra dan Doa Laut Nelayan Bajau di Pulau Maratua - Nina Queena Hadi Putri; Widyatmike Gede Mulawarman; Taqdiraa Taqdiraa (Aksara, 2026)
This study aims to analyze the semantic meanings embedded in the sea mantras and prayers of the Bajau community on Maratua Island, Berau Regency, East Kalimantan, and to reveal their ethnolinguistic implications for the belief system and worldview of the Bajau maritime society. This research employed a qualitative approach with an ethnolinguistic design. The data, consisting of sea mantras and prayer utterances, were collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, focusing on the identification of semantic fields, the analysis of lexical, connotative, and symbolic meanings, as well as the interpretation of metaphors and natural symbolism from semantic and ethnolinguistic perspectives. The findings reveal five major semantic fields, namely sea and nature, religiosity/Islam, safety, livelihood, and kinship. The Bajau ritual language contains complex layers of meaning through the use of metaphors and natural symbolism, such as the sea as an ancestor, the boat as a home, and water as a symbol of life and blessing. The study also shows a syncretism between Islamic teachings and local traditions in Bajau ritual practices. From an ethnolinguistic perspective, the mantras and sea prayers represent the Bajau cosmology that positions the sea as the center of life, a source of livelihood, a spiritual space, and a symbolic kinship entity that must be respected. This study confirms that ritual language functions not only as a medium of spiritual communication, but also as a representation of cultural identity, value systems, and the ecological relations of maritime communities. AbstrakPenelitian ini bertujuan menganalisis makna semantik dalam mantra dan doa laut masyarakat Bajau di Pulau Maratua, Kabupaten Berau, Kalimantan Timur, serta mengungkap implikasi etnolinguistiknya terhadap sistem kepercayaan dan pandangan dunia masyarakat maritim Bajau. Penelitian menggunakan pendekatan kualitatif dengan desain etnolinguistik. Data berupa tuturan mantra dan doa laut dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi. Analisis data dilakukan secara interaktif melalui reduksi data, penyajian data, dan penarikan kesimpulan dengan fokus pada identifikasi medan makna, analisis makna leksikal, konotatif, dan simbolik, serta interpretasi metafora dan simbolisme alam berdasarkan perspektif semantik dan etnolinguistik. Hasil penelitian menunjukkan adanya lima medan makna utama, yaitu laut dan alam, religius/Islam, keselamatan, rezeki, dan kekerabatan. Bahasa ritual Bajau mengandung lapisan makna yang kompleks melalui penggunaan metafora dan simbolisme alam, seperti laut sebagai leluhur, perahu sebagai rumah, dan air sebagai simbol kehidupan serta keberkahan. Temuan penelitian juga menunjukkan adanya sinkretisme antara ajaran Islam dan tradisi lokal dalam praktik ritual masyarakat Bajau. Secara etnolinguistik, mantra dan doa laut merepresentasikan kosmologi masyarakat Bajau yang menempatkan laut sebagai pusat kehidupan, sumber rezeki, ruang spiritual, dan kerabat simbolik yang harus dihormati. Penelitian ini menegaskan bahwa bahasa ritual tidak hanya berfungsi sebagai media komunikasi spiritual, tetapi juga sebagai representasi identitas budaya, sistem nilai, dan relasi ekologis masyarakat maritim.